Effect of work related variables on growth among working boys in Jordan. Issue 2 (1st February 2003) - Hawamdeh, H; Spencer, N
Abstract : Objective: To study the effect of work related variables on the height, weight, and body mass index (BMI) of working boys aged 10–16 years. Design: Cross sectional survey. Setting: Irbid, Jarash, and North Jordan Valley in Jordan. Participants: 135 working boys aged 10–16 years and their mothers. Outcome measures: Height for age z score; weight for age z score; BMI for age z score. Results: In bivariate analysis, child's duration of work ( r =−0.20), maternal height (r=0.26), and household per capita income ( r =0.23) were significantly correlated with height for age z score and duration of work ( r =−0.24), maternal height ( r =0.24), and household per capita income ( r =0.19) with weight for age z score. Duration of work (p<0.001), child's monthly income (p=0.044), maternal height (p=0.002), and household per capita income (p=0.005) were retained in the regression model fitted on height z score that explained 20.1% of the variance. The regression model fitted on weight z score explained 20.1% of the variance and duration of work (p<0.001), child's monthly income (p=0.022), household per capita income (p=0.017), and maternal height (p=0.004) were retained. Only duration of work (p=0.001) was retained in the model fitted on BMI for age z score. Conclusion: The results of this study suggest that the length of time children have been working and low monthly income have a detrimental effect on growth of working boys independent of the effects of low household per capita income and small maternal stature. Relevance of these findings for social policy and health care of working boys in Jordan and elsewhere is discussed.